The Hybridization of Vocational Training and Higher Education in Austria, Germany, and Switzerland - Graf, Lukas (Verlag Barbara Budrich, 2013)
Austria, Germany, and Switzerland are increasingly relying on hybridization at the nexus of vocational training and higher education to increase permeability and reform their highly praised systems of collective skill formation. This historical and organizational institutionalist study compares these countries to trace the evolution of their skill regimes from the 1960s to today's era of Europeanization, focusing especially on the impact of the Bologna and Copenhagen processes.